1998
DOI: 10.1111/j.1467-8624.1998.tb06166.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships and Self‐Esteem among Children Who Have Been Maltreated

Abstract: A prospective longitudinal design was employed to assess risks associated with maltreatment in a representative community sample of 107 maltreated children and an equal number of nonmaltreated comparison children. Heightened difficulties in peer relationships and self-esteem were associated with greater severity and chronicity of maltreatment. For example, children who experienced chronic maltreatment were less well-liked by peers. Type of maltreatment was also related to specific aspects of children's adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(170 citation statements)
references
References 73 publications
14
148
0
8
Order By: Relevance
“…The MCS (Barnett et al, 1993) has been shown to be an extremely reliable and valid measure for classifying child maltreatment typology (Bolger, Patterson, & Kupersmidt, 1998; English, Upadhyaya, Litrownik, Marshall, Runyan et al, 2005; Manly, 2005) that utilizes DHS records, specifying investigations and findings involving maltreatment in identified families over time. Rather than relying on case dispositions and official designations, the MCS codes all available information from DHS records, making independent determinations of maltreating environments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCS (Barnett et al, 1993) has been shown to be an extremely reliable and valid measure for classifying child maltreatment typology (Bolger, Patterson, & Kupersmidt, 1998; English, Upadhyaya, Litrownik, Marshall, Runyan et al, 2005; Manly, 2005) that utilizes DHS records, specifying investigations and findings involving maltreatment in identified families over time. Rather than relying on case dispositions and official designations, the MCS codes all available information from DHS records, making independent determinations of maltreating environments.…”
Section: Methodsmentioning
confidence: 99%
“…Experiencing multiple subtypes of maltreatment is a typical finding in maltreated populations (Bolger et al, 1998; Manly, Cicchetti, & Barnett, 1994; Manly et al, 2001) and is known to be especially deleterious to development. An increasing number of maltreatment subtypes experienced has been shown to be related heightened impulsive-like traits such as inappropriate affect, liability/negativity, reduced emotion regulation, (Shields & Cicchetti, 1998).…”
mentioning
confidence: 99%
“…Relatedly, dosing (or experiencing multiple types of maltreatment) of maltreatment experiences appears to matter across outcomes, and its impact can extend beyond the effects associated with experiencing a single maltreatment type, or the effects attributable to severity (e.g., Bolger et al, 1998, Bolger & Patterson, 2001). Flaherty and colleagues (2009) noted that exposure to five or more types of adversity (such as maltreatment experiences) in early childhood was associated with increased odds for health complaints and illness at age twelve.…”
Section: Measurement Problems Associated With Dimensions Of Maltreatmentmentioning
confidence: 99%
“…This contrasts with the more extensive literature examining the consequences of child maltreatment. Several studies have shown that earlier abuse and neglect experiences are more closely related to diminished well-being than is later maltreatment onset (Bolger, Patterson, & Kupersmidt, 1998; Manly, Kim, Rogosch, & Cicchetti, 2001; Putnam, 1997), although many scholars have contended that adolescent maltreatment is equally as pervasive and harmful as maltreatment during childhood (Brezina, 1998; Garbarino, Eckenrode, & Powers, 1997; Ireland et al, 2002). Of the studies that have examined the etiology of maltreatment, most have focused on early childhood risks (e.g., Berger & Brooks-Gunn, 2005; Connell-Carrick & Scannapieco, 2006).…”
Section: Introductionmentioning
confidence: 99%